(untitled) (Вестник КазНУ. Серия Востоковедения, 2017)
The article is devoted to studying wedding rituals of Turkic peoples, ritual songs, accompanying her it every action. As an integral component of such an important phenomenon of public, social and political significance in the life of any nation throughout the ages, musical and poetic samples of wedding procession between the Turkic peoples are a lot of communities. This, in turn, is indicative of the historical unity and kinship origins of modern Turkic ethnic groups, the realization of which is crucial in a globalized world, taking place in this century.